The Effect of Managerial Adverse Experience on Financial Reporting - Kubick, Thomas R.; Li, Yijun (The Accounting Review, 2023)
ABSTRACT We identify executives who have experienced significant accounting-related adverse events during their careers as a powerful setting to examine the extent to which prior professional experience can influence subsequent financial reporting policies. We find that firms led by senior financial executives who have experienced accounting-related adverse events during their careers exhibit greater unconditional accounting conservatism, a lower likelihood of experiencing future accounting-related adverse events, and less positive abnormal discretionary accruals. This effect tends to be stronger when the experience is more frequent, recent, severe, or proximate. Overall, our results reveal a meaningful relationship between managers’ professional experience and accounting policies. Data Availability: All data used in this study are obtained from publicly available sources. JEL Classifications: G40; M40; M41.